Water resources : efficient, sustainable and equitable use - Mauser, Wolfram (Sustainability project., 2009)
Water is a vital part of every ecosystem on the planet. It is a prerequisite for the basic function and productive efficiency of life on Earth. Today, approximately a third of the earth's population suffers because of water scarcity, and by the year 2025, this percentage is likely rise to two-thirds. This work shows what conflicts this will entail, and provides a basis for possible solutions. It is one of 12 books addressing global sustainability concerns commissioned by the Forum for Responsibility in Germany. The author first discusses what it is about water and its relationship to life that makes it unique. He then focuses on two areas where water usage has already caused severe environmental disruption (Aral Sea) or where the potential for international water conflicts is high (Nile River and its tributaries). The discussion on sustainable water use emphasizes the 1992 Dublin Statement on water, which emphasizes that it is a basic human right to have access to clean water and sanitation at an affordable price. Considering the depletion of surface and groundwater resources today in light of projected global population growth (9.5 billion by 2050), it is clear that providing water for individuals, agriculture, and industry will be one of humanity's biggest challenges for the future, requiring major improvements in water recycling and efficiency of use.